Dasar Hukum Bea Perolehan Hak Atas Tanah Dan Bangunan (BPHTB) Di Badan Pengelolaan Keuangan Dan Pendapatan Daerah (BPKPD) Kabupaten Buleleng - Febrinayanti Dantes, Komang; Ayu Apsari Hadi, I Gusti (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
This study aims to analyze the legal basis for the acquisition of land and building rights fees in Buleleng Regency. This research is a type of legal research with empirical juridical studies because this research deals with data. This research took place in Singaraja City, especially in the Regional Government Financial Management Agency (BPKPD) Buleleng Regency. Data were collected using observation and interview methods. The data analysis was conducted in a descriptive qualitative manner. Based on the results of the analysis, the legal basis for the Acquisition Fee for Land and Building Rights is relevant to the Regulation of the Minister of Finance, the collection of Fees for Acquisition of Land and Building Rights (BPHTB) is entirely carried out by the regions, this is due to policies on objects, subjects, rates, and tax bases fully stipulated by the Regional Government and adapted to the conditions and objectives of regional development. This policy is adjusted to the Regional Regulation of Buleleng Regency Number 1 of 2011 concerning Law Number 28 of 2009 concerning Regional Taxes and Regional Retributions for the regulation of the imposition of local taxes on Fees for Acquiring Rights on Land and Buildings (BPHTB).